PENGEMBANGAN JARINGAN LOCAL AREA NETWORK MENGGUNAKAN SISTEM OPERASI LINUX REDHAT 9 (Studi Kasus Pada Laboratorium Komputer SMA Negeri 1 Ujan Mas Kepahiang) - Sari, Herlina Latipa; sono, Aji Sudar; Hayadi, B Herawan (UNIVED Press, 2013)
Development Network Local Area Network Use PC Router Operating System Linux Redhat 9 At Laboratory Computer SMAN 1 Ujan Mas Kepahiang. This research aim to to develop Local Area Network network by using PC Router use system operate for Linux Redhat 9 at Laboratory Computer SMAN 1 Ujan Mas. With the existence of making of PC router use system operate for Linux Redhat 9, hence expense can be depressed by as cheap as possible, because such as those which we know costly marketing router price enough. With the existence of functioning router to continue data package and division of IP for the laboratory of very organizational other space and easy so that do not happened random in division of IP at SMA N laboratory 1 Ujan Mas Kepahiang.